Long-Term Outcome after Resection Rectopexy for Internal Rectal Intussusception. (30th December 2012) - Johnson, Egil; Kjellevold, Kristin; Johannessen, Hans-Olaf; Drolsum, Anders
Abstract : Background and Aims . The optimal treatment of patients with internal rectal intussusception (IRI) is unresolved. The aim was to study the short- and long-term outcome of resection rectopexy in these patients. Methods . An observational and mainly prospective study of 48 patients (44 women) with IRI who had ligament-preserving suture rectopexy by laparoscopic ( n = 25 ) or open ( n = 23 ) technique. Outcome measures were morbidity, scores for constipation and anal incontinence, patients' report, and health-related quality of life (HRQoL). Results . From preoperatively to a median of 6 months and 76 months postoperatively, constipation scores were reduced from a mean of (95% CI) 13.20 (11.41 to 15.00) to 6.91 (5.29 to 8.54) and 6.35 (4.94 to 7.76) ( P < 0.0001 ) . The number of constipated patients was reduced from 35 to eleven and eight, respectively, and none became constipated. Nine of ten symptoms of constipation improved. Corresponding scores for anal incontinence were 4.7 (2.4–7.0), 4.0 (2.4–5.7), and 4.1 (2.3–5.8), respectively. HRQoL at long-term followup compared to the general Norwegian population was reduced in four out of eight dimensions concerning physical factors. The patient-reported outcome at short- and long-term followup was improved by 85.4% and 75.0%, respectively. Conclusions . Resection rectopexy for IRI improved the outcome. HRQoL was reduced compared with the general population.